Socialization of Soil Vulnerability Map using Microseismic Method in Eastern Sleman, Yogyakarta - Wiji Raharjo; Ajimas Pascaning Setiohadiwibowo; Indriati Retno Palupi; Verty Deffian Supriyono; Arif Nor Aminah (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2019)
Community service activities are carried out in Depok District, Sleman Regency, Yogyakarta with preliminary survey stages, field data acquisition, data processing, data interpretation and socialization. The processing of the microseismic method is various, one of this method is the Horizontal to Vertical Spectral Ratio (HVSR) method. Processing of this HVSR method is to determine the natural frequency value and amplification value obtained at the time of acquisition so that it can be used to calculate the value of soil vulnerability. Based on the results of data processing, Depok District has a soft soil type where the soil is susceptible to vibration.Socialization is carried out in order to get more attention in infrastructure development or in accordance with the standards by the government. This is done to avoid the occurrence of severe building damage when hit by an earthquake.Keywords: Disaster-Prone Regional Socialization, Earthquakes, Microseismic, Soil vulnerability maps